Isolation and antifungal screening of endophytic fungi from Erigeron canadensis - Bai, Xuelian; Zhou, Ting; Lai, Tongfei; Li, Yicong; Chai, Jiale; Ni, Jiajun; Zhang, Huawei (Bangladesh Journal of Pharmacology, 2017)
Sixteen fungal strains isolated from the Erigeron canadensis, one of traditional Chinese medicines used to treat the pathogenic infection and dysentery, were evaluated for their antifungal activities against one human pathogen Candida albicans, and two phytopathogens, Colletotrichum fructicola and Rhizoctonia cerealis. The bioassay results indicated that the ethyl acetate extract of the fermentation broth of these fungal endophytes had stronger antimicrobial activities. Among these endophytic strains, the ethyl acetate extracts of strains NPR003 and NPR005 showed the strongest inhibitory effects and has potential application in the discovery of new antifungal agents. This was the first report on the isolation of endophytic fungi from E. canadensis and evaluation of their antifungal activities. Video Clip of Methodology: 1 min 4 sec Full Screen Alternate